2012
DOI: 10.1200/jco.2012.30.15_suppl.e15100
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of carcinoma in situ of the glans penis with topical chemotherapy agents.

Abstract: e15100 Background: To establish the response rate of 5-flurouracil (5-FU) and imiquimod (IQ) in the treatment of penile CIS in a large contemporary series in a supra-network center. The use of topical agents in the treatment of CIS of the penis has been well described in the literature. Previous studies have been limited by small sample size and imprecise end-points. Methods: Retrospective review of all primary and recurrent cases of penile CIS treated with 5-FU and IQ identified from a prospective database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
0
18
1
1
Order By: Relevance
“…The largest previous study which reported on 44 patients treated with topical 5‐FU as first‐line treatment showed a complete response rate of 57% , which is less than in our present study. These authors describe application of 5‐FU to the lesion for 12 h every 48 h over 28 days.…”
Section: Discussioncontrasting
confidence: 95%
“…The largest previous study which reported on 44 patients treated with topical 5‐FU as first‐line treatment showed a complete response rate of 57% , which is less than in our present study. These authors describe application of 5‐FU to the lesion for 12 h every 48 h over 28 days.…”
Section: Discussioncontrasting
confidence: 95%
“…Treatment of the primary tumour and the decision to proceed to inguinal lymph node dissection were established according to local protocols based on the 2009 EAU guidelines. For patients with penile carcinoma in situ (CIS), the European Association of Urology recommends topical chemotherapy with 5% fluorouracil and imiquimod (Alnajjar et al 2012). For Ta/T1 lesions, laser ablation is a valid treatment (Colecchia et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The best conservative treatment of primary penile carcinoma in situ (Tis) is topical therapy (recommendation, LE: 2b). The use of topical 5-fluorouracil (5-FU) or imiquimod can provide from 40.0% to 73.7% complete response (Alnajjar et al 2012;Lucky et al 2015), with circumcision performed before therapy (Lucky et al 2015). Patients presenting with non-invasive localized SCC (Ta) should be treated by partial glansectomy and resurfacing (recommendation, LE: 4).…”
Section: Tis and Ta Tumorsmentioning
confidence: 99%